PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI KELURAHAN KUALA KECAMATAN SINGKAWANG BARAT KOTA SINGKAWANG - Khairiansyah, Muhammdad; Zainal, Sofyan; Nugroho, Joko (JURNAL HUTAN LESTARI, 2018)
Mangrove forest in Kelurahan Kuala Disctrict of Singkawang Barat Singkawang City is utilized by the local residents to fulfill their needs. The relationship between the community and the existence of mangrove forest elicits specific perception on mangrove as an effort to maintain and preserve mangrove forests. This study aims to observe the perception from the community in Kelurahan Kuala District of Singkawang Barat Singkawang City on the existence of Mangrove forest and the factors influencing. The study used survey method, and the technique used was purposive sampling and proportional sampling. The total respondents are 94 persons. The results show that the level of people perception on the existence of mangrove forest in the coastal areas of Kelurahan Kuala belongs to moderate level, with 11 high perception respondents (12%), 67 moderate perception respondents (71%), and 16 low perception respondents (17%).Keywords: kelurahan kuala, mangrove forest, people perception,